Measuring synergies of banks' cross-border mergers by real options: Case study of Luminor Group AB - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2021)
Applying the real options valuation to measure merger and acquisition (M&A) synergy is highly debatable, with questions arising from the usefulness of this approach in real-world settings. Understanding the full benefits (and possible limits) of real options applications to measure synergy in cross-border merger activities remains a challenge. The main objective of the paper is to explore multiple types of synergies in the recent, highly strategic cross-border merger - the Luminor Group AB deal - and to value those synergies with the real options application. The research found that the sum of values of different types of synergies in M&A deals as the market value added provided by this deal could be valued with real options applications. A real options application may serve as a decision-making tool and at the same time be a useful valuation method of M&A deal synergies. The implications of this paper are twofold. First, the research contributes to corporate financing by providing relevant synergy measurement models in M&A deals. Second, the paper contributes to "grand challenges'' research topics of international businesses by illustrating how a group of multinational banks solved the problem of income inequality across countries, and balanced inequality within their networks through a cross-border merger.
Keywords: 330; real options; cross-border merger; synergies